Pelatihan Searching dan Drafting Paten Di Perguruan Tinggi Muhammadiyah Mataram - Sofyan Arief; Agus Zainudin; Achmad Fauzan HS (Universitas Muhammadiyah Malang, 2021)
Dalam pelaksanaan pengabdian ini kami memberikan pemahaman dan pelatihan akan searching dan drafting paten sesuai kebutuhan dari peserta. Untuk searching kami berikan dengan menunjukkan pilihan metode dalam searching paten beserta kegunaannya, seperti searching untuk mencari state of the art, searching untuk mencari perusahaan pesaing, searching untuk mencari peneliti pada bidang yang sama, termasuk metode khusus dalam searching untuk pencarian data bidang farmasi. Setelah memahami searching baru kami memberikan materi tentang drafting paten, metode yang kami gunakan adalah metode pembelajaran dengan pemberian materi, diskusi diikuti melakukan praktik searching dan drafting paten, metode ini terbukti efektif karena mampu meningkatkan pemahaman peserta akan searching dan drafting paten. Pelatihan searching dan drafting paten ini dilakukan dalam rangka meningkatkan pemahaman peserta dan peningkatan pendaftaran kekayaan intelektual khususnya paten. Metode searching dan drafting paten memang bukanlah hal yang mudah untuk dipelajari sehingga pasti kedepan masih dibutuhkan penguatan penguatan bagi peserta dengan mengikuti pelatihan lanjutan, dengan metode pemberian materi diikuti dengan pelatihan menjadikan proses ini berjalan dengan efektif. Patent Searching and Drafting Training At Muhammadiyah University of Mataram. In the implementation of this service, we provide understanding and training on searching and drafting patents according to the needs of participants. For searching we provide by showing methods for searching patents and their uses, such as searching for state of the art, searching for competing companies, searching for looking for researchers in the same field, including special methods in searching for data searching in the pharmaceutical field, after understanding the new searching we provide material about patent drafting, the method we use is the learning method by providing material, discussion followed by the practice of searching and drafting patents, methods This has proven to be effective because it is able to increase participants' understanding of patent searching and drafting, this training on patent searching and drafting is carried out in order to increase participants' understanding and increase intellectual property registration, especially patents, patent searching and drafting methods are effective. g is not an easy thing to learn so that in the future there will still be a need for strengthening reinforcement for participants by attending further training, with the method of providing material followed by training to make this process run effectively.